Blue Accounting : Keberlanjutan Terumbu Karang Di Pantai Jemeluk - Negara, Dhimas Putra; Darmawan, Nyoman Ari Surya (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
PThis study aims to determine how the application of blue accounting in the care of coral reefs at Jemeluk beach to maintain its sustainability. This research was conducted on Jalan Amed Seraya-Jemeluk, Purwakerti Village, Abang District, Karangasem Regency. The research method used in this research uses qualitative methods. The subject of this research is the sustainability of coral reefs at Jemeluk beach. The subjects of this research are parties who can be asked for information and also understand the issues being studied. In this study, the authors used a purposive sampling technique where sampling was carried out with certain considerations. The considerations included that the informants knew or were directly involved in managing the sustainability of coral reefs at Jemeluk beach. The informants in this study were caretakers of coral reefs at Jemeluk beach. While the object in this study is blue accounting: the sustainability of coral reefs at Jemeluk beach. The results of this study are the application of blue accounting to the activities of the company activities can help as an effort to reduce environmental problems. The application of blue accounting helps in revealing the environmental problems faced. The application of blue accounting is very helpful for companies in the reporting process related to environmental conservation records, namely planting coral reefs.Â Â